A friction-wear correlation for four-ball extreme pressure lubrication - Chan, Chung-Hung; Lim, Wen Huei; Yeong, Shoot Kian; Kow, Kien Woh; Ho, Yong Kuen (American Society of Mechanical Engineers (ASME), 2019)
A first-ever friction-wear model for Four-Ball Extreme Pressure (EP) Lubrication test (ASTM D2783) is presented in this work. The model considers the rate of entropy generation and dissipation within the lubricated tribosystem to establish the friction-wear correlations for 12 lubricating oils comprising minerals, esters and other formulated oils. The correlations can be used to calculate the probability to pass/fail in the EP lubrication. The probability has similar trend as load-wear index from ASTM D2783 method. Besides, the friction-wear correlations allows quick estimation of EP performance of an unknown lubrication, upon comparing with that of an established one. The methods demonstrated here will help researchers or lubricant technologist to characterize the EP behavior quickly without over-relying on tribotester.